Analisis Kadar Kalium (K) dan Posforus (P) Pada Limbah Kangkung Darat (Ipomea reptans Poir) - Setianingsih, Rahmadiana; Nuryanti, Siti; Ratman, Ratman (Universitas Tadulako, 2018)
This research is aimed to determine potassium (K) and phosphorus (P) levels in the waste of swamp cabbage. The Spectrodirect instrument was used to analyze the levels of potassium and phosphorus in the waste of swamp cabbage. Based on analysis of the levels of potassium and phosphorus in the waste of swam cabbage, it was obtained that the average value of K concentration in the sample was 5.51213 mg/kg. On the other hand, the average value of P concentration in the sample was 43.19503 mg/kg. From the result of this analysis, it also demonstrated that the concentration of phosphorus was higher than the concentration of potassium.